Archeologia, pamięć, sztuka. Archeoetnografia i sztuka okopowa związana z obozem jeńców wojennych i internowanych w Tucholi, woj. kujawsko-pomorskie - Kobiałka, Dawid (Folia Praehistorica Posnaniensia, 2019)
Lidar-derivatives gathered during the realization of IT System of Country’s Protection Against Extreme Hazards (so-called ISOK programme) have initialized the non-invasive archaeological research concerning the preservation of the relicts of the former prisoner of war and internment camp in Tuchola, Poland. The camp functioned during the Great War (1914–1918) and the Polish-Soviet War (1919–1921). This paper discusses and summaries the preliminary results of this research. It argues that the use of ethnographic methods can supplement and enrich the historical records related to the camp. The article discusses in detail the assemblage of material culture made, remade, or personalized by prisoners and internees documented during the research. These artefacts are unique examples of trench art. Discussion concerning the objects is the main goal of this paper. They are the first examples of the trench art related to the Tuchola camp analyzed in the archaeological literature.